1998
DOI: 10.1002/(sici)1099-0879(199812)5:4<216::aid-cpp165>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

A psychological re-analysis of the scientist-practitioner model

Abstract: For decades, NHS clinical psychologists have struggled to implement the scientist±practitioner model of professional practice. The pressure for effectiveness and efficiency in health services internationally, and the advent of the NHS research and development (R & D) strategy in the UK make this a suitable moment to reframe this model, in favour of the more attainable, complementary and timely approaches of empirical clinician',`evaluative clinical scientist' and`clinical scientist'. As well as being harmoniou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This is recognised by the Department of Health's own emphasis on implementing research findings (Department of Health, 1995), which includes a range of interventions designed to foster quality, including audit and continuing professional development. Unfortunately, the evidence to date would indicate that such methods will have limited impact on the quality of care (Milne and Paxton, 1998). For instance, although some studies of the impact of feedback and audit have indicated some success (Walshe and Buttery, 1995;Hearnshaw et al, 1998), rigorous evaluations of the results of completing audit cycles have arrived at more pessimistic conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…This is recognised by the Department of Health's own emphasis on implementing research findings (Department of Health, 1995), which includes a range of interventions designed to foster quality, including audit and continuing professional development. Unfortunately, the evidence to date would indicate that such methods will have limited impact on the quality of care (Milne and Paxton, 1998). For instance, although some studies of the impact of feedback and audit have indicated some success (Walshe and Buttery, 1995;Hearnshaw et al, 1998), rigorous evaluations of the results of completing audit cycles have arrived at more pessimistic conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…2``Evaluative scientist'' (conducting pragmatic research on development and implementation issues). 3``Empirical clinician'' (who consumes and applies research, including participation in audit) (Milne and Paxton, 1998).…”
Section: Introductionmentioning
confidence: 99%